STUDI KELEMBAGAAN DALAM PENGELOLAAN DAN PEMANFAATAN TELUR IKAN TERBANG (KASUS DESA PA’LALAKANG KABUPATEN TAKALAR) - Yusuf, Jumran; Rukmana, Didi; Ali, Syamsu Alam; Indar, Yusran Nur (Torani Journal of Fisheries and Marine Science, 2014)
The aim of the research was to determine the fungsional of institution on utilization and management of flying fish eggs at Pa’lalakang Village, Takalar Regency. This study using qualitative research approach thatcharacterize as empirical cualitative and descriptive. Data was collected through in depth interview,observation and literature study. The result showed that the function of intstitution have been internalization onutilizing and managing of flying fish egg at Pa’lalakang Village, that including function in adaptation onutilization and management of flying fish. Those aspect have been implemented by fishermen community. Thestudy also found that achievement function was focus on goverment institution, social integration function wason community institution and maintenant function of culture was on fisherman household. Keywords: Flying fish egg, institution, utilization, and management